Can Grassroots Organizations Reduce Support for Right-Wing Populism via Social Media? - Johannes Wimmer; Leonhard Vollmer (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
The rise of right-wing populism throughout Western democracies coincided with an increasing adoption of social media – both among supporters and opponents of right-wing populism alike. In light of these trends, we assess whether grassroots organizations are effective in combating right-wing populism via social media. We study this question using a tightly controlled online field experiment embedded in the Facebook campaign of a German grassroots organization. Leveraging geo-spatial variation in where the organization disseminated its Facebook ads targeting Germany's leading right-wing populist party (AfD), we find that the campaign did not significantly affect the AfD's vote share and turnout. Drawing on data from a complementary online experiment, we show that insufficient outreach on Facebook together with the absence of individual-level responses of attitudes and behavior explains why the campaign did not meaningfully shape aggregate election outcomes.
Keywords: 330